Negative news and the stock market impact of tone in rating reports - Löffler, Gunter; Norden, Lars; Rieber, Alexander (Journal of Banking & Finance, 2021)
We investigate whether the stock market impact of tone in Moody's rating reports depends on negative news. Reports convey negative news through negative rating actions (downgrades, reviews for downgrade or negative outlooks) or negative tone if there is no rating action. Using data from U.S. firms during 1995–2016, we find a significant short-term market impact of tone in reports with and without rating actions. The impact of tone is about five times stronger for negative rating actions but reversed in post-event time. The short-term impact of tone in reports with negative rating actions holds for different levels of investor attention and investor sentiment. The return reversal is driven by low-rated firms and stronger when sentiment is high and attention low. Finally, the predictability of future downgrades by tone is reduced for negative rating actions but not for reports without rating actions. The evidence is novel and indicates that negative news amplifies the market impact of tone and induces overreaction to negative rating actions.